KARAKTERISTIK DAN MOTIVASI WISATAWAN NUSANTARA BERWISATA KULINER DI UBUD, BALI - Intan Diah Angreni, Ni Putu; Wijaya, NMS.; Citra Juwitasari, W. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 2 (2024): Jurnal IPTA (December 2024), 2025)
Ubud is the first destination to have branding as a UNWTO standard culinary tourism destination with the best endorsers in the world for the tourism sector. The research objective is related to the motivations and characteristics of domestic tourists undertaking culinary tourism in Ubud, Bali, to provide a deeper view of market segments and consumer preferences. These can include food tours, cooking classes, food festivals and interactions with local communities, all of which can increase a destination's appeal. The sampling technique uses a purposive sampling technique by distributing 100 questionnaires to domestic tourists who will, are currently and have already gone on culinary tourism in Ubud. This research uses quantitative descriptive research methods. Data that has been processed will use a Likert scale and then be presented in the form of numbers. Based on research results, domestic tourists who undertake culinary tourism in Ubud are dominated by tourists from the Java region (54%) are male (52%) aged 15-30 years (90%) have a high school/vocational school education (51%) are unmarried (84%) not yet working (50%) social media information sources (76%) with an average expenditure of IDR 150,000 – IDR 500,000 (56%). The motivation of domestic tourists to undertake culinary tourism is dominated by the motivation to try new food (average score 4.10), relax, and enjoy a balance between quality and price (average score 4.0), as well as social and interpersonal factors (average score- average 3.65).